The rise of the syndrome – sub‐optimal growth disorders in farmed shrimp. (1st March 2021) - Kooloth Valappil, Rajendran; Stentiford, Grant D.; Bass, David
Abstract: The phenomenon of slow growth in farmed shrimp was observed for the first time in 1989 in Penaeus vannamei as a clinical manifestation of runt deformity syndrome caused by infectious hypodermal and hematopoietic necrosis virus. Subsequently, it was recorded in Penaeus monodon during 2001–2002. Since then, the condition described as monodon slow growth syndrome (MSGS) has been reported from many countries. Though not leading to mortality, retarded growth at the pond level results in significant economic losses. Several potential pathogens have been identified from affected shrimp; however, no confirmed causal relationship has yet been established. Initially, P. vannamei farmed alongside slow growth‐affected P. monodon were unaffected by the condition. Further, experimental studies suggested that P . vannamei was not susceptible. However, in recent years, increasing incidence of severe growth retardation has been reported in farmed P. vannamei . Currently, slow growth is considered as one of the most impactful production‐limiting conditions affecting shrimp farming across Asia. Similar to MSGS, many infectious agents have been detected in slow growth‐affected P. vannamei, especially the microsporidian Enterocytozoon hepatopenaei . Further, genetic and environmental factors have been suggested to play a role. However, the exact cause of slow growth remains elusive, proposing that it may be a multi‐factor syndrome. This review tracks the trajectory of the condition over the period of significant expansion of shrimp farming and postulates that conventional single pathogen/single disease paradigms are insufficient to deal with chronic yield‐limiting syndromes. We suggest more realistic, multi‐dimensional aetiological consideration of syndromic and emerging diseases in shrimp aquaculture.